GreenCompass - A self-assessment tool for fostering integration of green skills - Jovanovski, Bojan; Shamsuzzoha, Ahm; Polenakovikj, Radmil; Velkovska, Mila; Velkovski, Trajce (European Academy of Sciences and Arts, 2024)
In today's ever-evolving landscape, fostering green skills emerges as a paramount endeavour, a beacon of progress towards a green(er) future. Within this transformative journey, this paper unveils a blueprint for organizations and institutions seeking to embrace a green future. The Self-Assessment Tool, GreenCompass, emerges as a pivotal cornerstone of this research, designed to quantitatively assess the green innovation capabilities of VET organizations. This tool offers a comprehensive view of an organization's readiness and potential for fostering green skills for green innovation. The paper further unveils the insights garnered from the extensive pilot-testing of the GreenCompass across diverse geographical regions and within various types of vocational education and training institutions, validating its applicability for a broad spectrum of settings. In the last part, the paper emphasizes the creation of an environment, a nurturing environment wherein green skills can thrive. It's a conceptual framework dedicated to facilitating the growth of a sustainable and green mindset, in alignment with the evolving dynamics of the green transition. This journey underscores the significance of a comprehensive methodology, one that begins with self-assessment, evolves through empirical validation, and culminates in the establishment of an environment to nurture green innovation. Ultimately, this multifaceted approach propels organizations towards a future characterized by innovation, sustainability, and an un-wavering commitment to a greener, more eco-conscious world.
Keywords: green innovation; self-assessment tool; green skills environments; vocational education and training (VET); vocational excellence; knowledge transfer; fi=Tuotantotalous|en=Industrial Management|